Comparison the Results of Humerus Shaft Fractures Treated by Functional Bracing versus Dynamic Compression Plate (Medicine Today, 2024)
Introduction with Objective: To compare the results of humerus shaft fractures treated by functional bracing and dynamic compression plate. Materials and Methods: This experimental study was carried out at the Department of Orthopedic Surgery at Chittagong Medical College Hospital, Chattogram from August 2019 to July 2021. All adult patients of closed diaphyseal fracture of humerus attending the Orthopaedics department, Chittagong Medical College Hospital during study period were the study population. Purposive sampling was done according to availability of the patients. Cases were divided in two groups; group A (dynamic compression plate) and group B (functional bracing). All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. The results were expressed as percentage and mean ± SD and p